Minimally Invasive Gynecology An Evidence Based Approach (Springer International Publishing, 2018)
In the last 25 years, minimally invasive surgery techniques have had a great impact on all gynecologic surgery areas, becoming the technique of choice in most leading health centers around the world. Nowadays, due to such developments, the employment of minimally invasive techniques is a feature for every gynecological surgery service, being part of their daily routine. To the same extent, it is a requirement for every gynecological surgeon to be aware and up to date regarding these techniques and their uses. The book describes and discusses minimally invasive techniques in gynecological surgery by means of an evidence-based analysis, providing clinical correlations for a practical purpose. Techniques covered include vaginal radical trachelectomy, laparoscopic radical hysterectomy, robotic surgery in gynecological cancer, hysteroscopic myomectomy, LESS surgery, deep endometriosis surgery, and laparoscopic supra cervical hysterectomy. Some of the most renowned international references in minimally invasive surgery are included in this title, making Minimally Invasive Gynecology: an Evidence Based Approach fundamental reading for all gynecologists and gynecological surgeons.